Common sense and resistance: EMI policy and practice in Indonesian universities - Coleman, Hywel; Ahmad, Nur Fauzan; Hadisantosa, Nilawati; Kuchah, Kuchah; Lamb, Martin; Waskita, Dana (Current issues in language planning, 2024)
Research on English Medium Instruction (EMI) in Higher Education (HE) has tended to have a technicist orientation, examining for example how it is implemented and the challenges it has encountered. Much less critical attention has been given to the rationales that language policy makers and other stakeholders offer for introducing EMI - the drivers may be reported (e.g. Rose et al., 2020, in China; Galloway & Sahan, 2021, in Vietnam and Thailand) but they are rarely questioned. Here, we focus on these rationales, using data from a research project which monitored the spread of EMI through Indonesian HE. Managers at 24 institutions were surveyed along with 281 lecturers who taught their subject in the medium of English at 41 universities. In the stakeholders' responses, we identified four common sense assumptions (Gramsci, 1971) about English and its role in Indonesia that often underlay their justifications for introducing EMI. We also noted some signs of resistance to EMI which demand further empirical investigation. This case reminds us that public language policy should be based on careful analysis of needs at national and institutional levels. Selama ini penelitian yang fokus pada penggunaan Bahasa Inggris sebagai bahasa pengantar (English Medium Instruction/EMI) di Perguruan Tinggi (PT) cenderung terbatas pada hal-hal teknis saja, misalnya implementasi dan tantangan yang dihadapi. Masih amat sedikit penelitian yang menelusuri pemikiran para perancang kebijakan bahasa-dalam-pendidikan dan pemangku kepentingan lainnya terkait EMI. Studi ini berfokus pada pemikiran tersebut dengan menggunakan data dari suatu proyek penelitian yang memetakan penyebaran EMI pada perguruan tinggi di Indonesia. Survei melibatkan pimpinan 24 perguruan tinggi dan 281 dosen non-Bahasa Inggris di 41 universitas yang mengajarkan mata kuliah masing-masing dengan Bahasa Inggris sebagai bahasa pengantar. Berdasarkan respons para pemangku kepentingan, kami mengidentifikasi empat asumsi akal sehat (Gramsci, 1971 ) tentang bahasa Inggris dan perannya di Indonesia yang sering dikemukakan sebagai alasan untuk menerapkan EMI. Kami juga mencatat adanya indikasi resistansi terhadap EMI; gejala tersebut butuh penyelidikan lebih lanjut. Kasus ini mengingatkan kita bahwa kebijakan bahasa resmi perlu didasarkan pada analisis yang cermat pada aras nasional maupun institusional.